2021
DOI: 10.21203/rs.3.rs-148149/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nuclear Morphology Optimized Deep Hybrid Learning (NUMODRIL) For Accurate Diagnosis and Prognosis of Ovarian Cancer

Abstract: Nuclear morphological features are potent determining factors for clinical diagnostic approaches adopted by pathologists to analyse the malignant potential of cancer cells. Considering the structural alteration of nucleus in cancer cells, various groups have developed machine learning techniques based on variation in nuclear morphometric information like nuclear shape, size, nucleus-cytoplasm ratio and various non-parametric methods like deep learning have also been tested for analysing immunohistochemistry im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…While Judson (1991) defined it as a process where transformation or change occurs in an organization through culture, others assume it to be a process of organizational restructuring to meet the current demands. Sengupta et al (2006) defines organizational change as "the adoption of a new idea or behavior". According to him organizational change occurs when an organization modifies its existing structure to increase effectiveness and to achieve the objectives.…”
Section: Change Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…While Judson (1991) defined it as a process where transformation or change occurs in an organization through culture, others assume it to be a process of organizational restructuring to meet the current demands. Sengupta et al (2006) defines organizational change as "the adoption of a new idea or behavior". According to him organizational change occurs when an organization modifies its existing structure to increase effectiveness and to achieve the objectives.…”
Section: Change Managementmentioning
confidence: 99%
“…These "change theories" provide a basic guideline for directing the change management process. A few studies have shown that the incorporation as well as integration of change models during the implementation process will lead to enhancement in their perception and their level of involvement (Lewis, 2011;Sengupta et al, 2006).…”
Section: Change Managementmentioning
confidence: 99%